2016
DOI: 10.1080/01658107.2016.1257640
|View full text |Cite
|
Sign up to set email alerts
|

Heroin-Induced Exodeviation Masking a Baseline Decompensated Esophoria

Abstract: Heroin and other opiate intake have been shown to have various effects on the brain, including the documentation of a small number of cases of strabismus from intake and withdrawal. Prior reports of heroin have focused on its tendency to cause diplopia, especially esodeviation upon withdrawal. The authors describe a 25-year-old woman who developed double vision from a decompensated esophoria where heroin use induced an exodeviation that transiently improved her diplopia. Measurements after acute heroin use con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Although there are no reports on hydromorphone causing ocular misalignment, there have been rare case reports of exotropia and diplopia associated with the onset of heroin use. 5,6,8,9 It is unclear if and how the mechanism behind heroin and diplopia is related to hydromorphone and diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reports on hydromorphone causing ocular misalignment, there have been rare case reports of exotropia and diplopia associated with the onset of heroin use. 5,6,8,9 It is unclear if and how the mechanism behind heroin and diplopia is related to hydromorphone and diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, similar to how opiate withdrawal can cause esotropia, opiate use may also cause exotropia, or the outward deviation of the eyes. To the best of our knowledge, there are four documented cases of exotropia in active opiate users; however, the sparsity of the literature on this topic is likely due to difficulty in gaining access to patients at the time of illegal drug use [13,17,32]. Notably, the patient in a study conducted by Hakimi et al reported experiencing horizontal binocular diplopia for 3 months, which the authors suspect was due to heroin-induced exotropic deviation, prior to presentation for acute onset esotropia 2 days following last heroin use [13].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are four documented cases of exotropia in active opiate users; however, the sparsity of the literature on this topic is likely due to difficulty in gaining access to patients at the time of illegal drug use [13,17,32]. Notably, the patient in a study conducted by Hakimi et al reported experiencing horizontal binocular diplopia for 3 months, which the authors suspect was due to heroin-induced exotropic deviation, prior to presentation for acute onset esotropia 2 days following last heroin use [13]. A proposed mechanism by which this may occur is that the ability of opiate use to decrease the drive for accommodative convergence may lead to a relative overcompensation through which an exotropic deviation can manifest.…”
Section: Discussionmentioning
confidence: 99%